2003
DOI: 10.3104/reports.137
|View full text |Cite
|
Sign up to set email alerts
|

Performing movement sequences with knowledge of results under different visual conditions in adults with Down syndrome

Abstract: -The purpose of this study was to examine the learning of movement sequences in individuals with Down syndrome under different visual information conditions. 10 adults with Down syndrome and 14 neurologically typical adults performed a sequence of movements under two different visual information conditions: full visual feedback of the limb and environment and no visual feedback of the limb. Participants were given knowledge of results of their total movement time after each trial. The entire task was presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…It may be the case that individuals with DS are unable to discriminate between gross motor movements as well discriminate differences of movement velocities, or attribute functionality to particular movements [29,35]. In addition it may be that an important attribute of motor dysfunction in DS individuals pertains to the inability to quickly combine visual and motor inputs [30,55]. Our results build on these previous findings, as we show that the discrimination of biological motion portraying the same actions produced at different speeds is also impaired in Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be the case that individuals with DS are unable to discriminate between gross motor movements as well discriminate differences of movement velocities, or attribute functionality to particular movements [29,35]. In addition it may be that an important attribute of motor dysfunction in DS individuals pertains to the inability to quickly combine visual and motor inputs [30,55]. Our results build on these previous findings, as we show that the discrimination of biological motion portraying the same actions produced at different speeds is also impaired in Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, evidence exists to suggest that children with DS exhibit deficiencies in coupling visual information to motor output [29]. Research by Virji-Babul et al [30] suggests that individuals with DS demonstrate impairments when combining visual and motor information. For example, when stepping over an object child with DS exhibited reduced step length variability compared to typically developed controls and tended to stop in front of objects before stepping over them.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside structural/anatomical differences it has also been reported that people with DS perform poorly in most areas of motor functioning, for example finger-pressing (Latash, Kang, and Patterson, 2002), reaction timing (Virji-Babul, Lloyd, and Van Gyn, 2003), and in oral functions such as chewing and swallowing (Frith and Frith, 1974;Spender et al, 1995;Spano, Mercuri, Rando, Panto, Gagliano, Henderson, and Guzzetta, 1999) and particularly motor control in speech production (Kumin, 1994). Recent research (Barnes, Roberts, Mirrett, Sideris, and Misenheimer, 2006) provided detailed information on oral-motor development in DS, finding that boys with DS showed significantly lower levels of lip, tongue, velopharynx, larynx, and coordinated speech function than typically developing boys and lower levels of coordinated speech movements when compared with children with Fragile X, another condition which involves intellectual disability.…”
Section: Structural and Motoric Differences In Down's Syndromementioning
confidence: 99%